STRATEGI DINAS SOSIAL TERHADAP PEMBERDAYAAN PENYANDANG DISABILITAS DI KABUPATEN SINJAI (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study aims to find out: (1) Social Service Strategies for the empowerment of persons with disabilities in Sinjai Regency (2) Supporting and inhibiting factors for the empowerment of persons with disabilities in Sinjai Regency. The type of research used is a type of descriptive qualitative research. The data source of this study was obtained from the Head of the Social Service of Sinjai Regency, the Head of Rehabilitation and Social Empowerment. The data collection methods used are observation, interviews, and documentation. Data analysis used for data collection, data reduction, data presentation and conclusion drawn. The results of the study show that: The Social Service Strategy for the empowerment of persons with disabilities in Sinjai Regency by using 4 Strategies, namely: assessment and outreach, distribution of social assistance which includes: business capital assistance, livestock business assistance, assistance with assistive tools, cash assistance, provision of special facilities for persons with disabilities, and holding social guidance, including skills training and productive economic business guidance (UEP). The inhibiting factors are the lack of human resources so that it is still very limited in implementing empowerment strategies, lack of involvement of people with disabilities, and budget limitations. The implications of this research show the importance of enthusiasm for people with disabilities in the empowerment process so that they can coexist with the community, as well as the importance of coordination between the social service and stakeholders in terms of increasing the budget so that they can maximize assistance and play a more active role in implementing strategies by paying special attention to people with disabilities equally. The same has implications for future researchers.